Áreas verdes e parques urbanos em Fortaleza/Ceará – usos múltiplos das águas em ambientes lacustres - Ribeiro, Lucas Emerson Uchôa (2023)
This work discusses the green and blue areas in Fortaleza, Ceará, focusing on the urban parks of the lagoons, and their respective multiple uses of water resources. The objective of this work is to discuss the green areas through the urban parks of the Fortaleza lagoons, identifying and categorizing the typologies of multiple uses of the water present in the lagoons, highlighting the Lagoa da Viuva Park as a test area. The theoretical basis of this work was organized with a sequence of concepts to the understanding of the proposed objectives: urban green areas; Urban parks and legally protected areas; Landscape and Urban Lakers; and typologies of multiple uses in water resources. Regarding the methodology, a division was presented into four steps: 1) bibliographic and documentary surveys; 2) cartographic surveys; 3) Surveys of the typologies of use of lagoons' water resources; 4) Preparation and integration of database and inventories, in addition to the systematization of research results and conclusions. As a result, 102 lagoons were identified in Fortaleza: 92 current and 10 grounded, of which 62 are not considered as legally protected areas, in addition to permanent preservation areas in the riparian forest and environmental protection zones. In addition, the constitution of 15 more urban parks among the identified lagoons was indicated. Subsequently, consumer uses (desedentation of animals and irrigation) and non-consumption (fishing, recreation, fauna and flora protection and dilution of organic matter) of the Viúva and Varjota Lakers were measured, as well as the comprehensive, competitive and linked/competitive uses of water.